2020
DOI: 10.3390/ijms21197336
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Extracellular Vesicles in the Pathophysiology of Multiple Sclerosis

Abstract: Extracellular vesicles (EVs) represent a new reality for many physiological and pathological functions as an alternative mode of intercellular communication. This is due to their capacity to interact with distant recipient cells, usually involving delivery of the EVs contents into the target cells. Intensive investigation has targeted the role of EVs in different pathological conditions, including multiple sclerosis (MS). MS is a chronic inflammatory and neurodegenerative disease of the nervous system, one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 106 publications
0
27
0
3
Order By: Relevance
“…Datta Chaudhuri et al [ 43 ] identified a stimulus-dependent protein composition of ADEVs implicated in the support of neurite outgrowth and neuronal survival following ATP or IL-10 stimulation and, conversely, an enrichment in proteins supporting immune cell infiltration following treatment with the pro-inflammatory cytokine IL-1β. Although it has been demonstrated that EVs contribute to neuroinflammation and neurotoxicity in MS [ 44 ], to our knowledge, no data are available on the protein composition of ADEVs shed in response to T cell soluble factors [ 40 ]. Astrocyte reaction contributes to the remyelination process in MS through the secretion of soluble factors that both support and inhibit oligodendrocyte progenitor cell proliferation, differentiation, and migration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Datta Chaudhuri et al [ 43 ] identified a stimulus-dependent protein composition of ADEVs implicated in the support of neurite outgrowth and neuronal survival following ATP or IL-10 stimulation and, conversely, an enrichment in proteins supporting immune cell infiltration following treatment with the pro-inflammatory cytokine IL-1β. Although it has been demonstrated that EVs contribute to neuroinflammation and neurotoxicity in MS [ 44 ], to our knowledge, no data are available on the protein composition of ADEVs shed in response to T cell soluble factors [ 40 ]. Astrocyte reaction contributes to the remyelination process in MS through the secretion of soluble factors that both support and inhibit oligodendrocyte progenitor cell proliferation, differentiation, and migration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the possibility for the EVs to cross both undamaged and disrupted BBB, EVs could be detected in different biological fluids and represent a new class of biomarkers (Verderio et al, 2012 ; Galazka et al, 2017 ) and be also implicated in some stage of MS development and pathogenesis (Dolcetti et al, 2020 ).…”
Section: Evs In Cns and Neuroinflammationmentioning
confidence: 99%
“…As membranous vectors of intercellular communication secreted by cells into the extracellular space, EVs are capable of influencing physiological and pathophysiological functions by trafficking bioactive cargoes such as proteins, lipids, and nucleic acids to recipient cells (van Niel et al, 2018;Xiao et al, 2021). EVs originating from various cell types are understood to influence the pathogenesis of MS and EAE (Dolcetti et al, 2020), highlighting their utility as biomarkers of disease. Conversely, exogenous stem cell-derived EVs act as delivery vehicles for prospective therapeutic factors (Wiklander et al, 2019), even demonstrating the ability to cross the BBB (Jan et al, 2017;Banks et al, 2020).…”
Section: Mechanisms Of Action For Non-hematopoietic Stem Cellsmentioning
confidence: 99%